Floral Color, Anthocyanin Synthesis Gene Expression and Control in Cape Erica Species - Le Maitre, N C; Pirie, Michael David; Bellstedt, Dirk U. (Frontiers in Plant Science, 2019)
Introduction: The Cape Floristic Region (CFR) is a biodiversity hotspot, recognized globally for its unusually high levels of endemism. The origins of this biodiversity are a long-standing topic of research. The largest “Cape clade,” Erica, radiated dramatically in the CFR, its ca. 690 species arising within 10–15 Ma. Notable between- and within-species flower color variation in Erica may have contributed to the origins of species diversity through its impact on pollinator efficiency and specificity. Methods: We investigate the expression and function of the genes of the anthocyanin biosynthesis pathway that controls floral color in 12 Erica species groups using RT-qPCR and UPLC-MS/MS. Results: Shifts from ancestral pink- or red- to white- and/or yellow flowers were associated with independent losses of single pathway gene expression, abrogation of the entire pathway due to loss of the expression of a transcription factor or loss of function mutations in pathway genes. Discussion: Striking floral color shifts are prevalent amongst the numerous species of Cape Erica. These results show independent origins of a palette of mutations leading to such shifts, revealing the diverse genetic basis for potentially rapid evolution of a speciation-relevant trait.